The care of people with disabilities in Mexican and Spanish universities - Guadalupe Palmeros y Ávila; Joaquín Gairin Sallán (Pontificia Universidad Católica del Perú, 2016)
Worldwide, the subject of inclusion in higher education has become more important in recent years and has brought about actions for the full inclusion of students. In this work the substantive and contextual aspects that are present in Mexican and Spanish universities to the attention of students with disabilities are analysed, considering the historical development axis of the process of inclusive education in both countries and identifying similarities, differences, needs and deficiencies to the attention of those students. Likewise the different programs and actions that have to finally make some considerations to overcome some factors that still persist and limit the effectiveness in dealing with diversity and integration of the group of persons with disabilities will be analysed.